Prognostic value of serum Mrp 8/14 in sepsis-induced acute respiratory distress syndrome patients: a retrospective cohort study - Caizhi Sun; Yongpeng Xie; Chenchen Zhu; Lei Guo; Bowen Xu; Haidong Qin; Xiaomin Li (PeerJ)
Background Mrp 8/14 is abundantly secreted by activated neutrophils during infection and inflammation. However, its prognostic value in acute respiratory distress dyndrome (ARDS) induced by sepsis is poorly understood. Our aim was to investigate the relationship between serum Mrp 8/14 and the prognosis in sepsis-induced ARDS patients admitted to the intensive care unit (ICU). Methods Serum Mrp 8/14 concentrations were analyzed in 118 ARDS patients induced by sepsis included in the analytical study. Patients were enrolled upon admission to the ICU of Nanjing Hospital affiliated to Nanjing Medical University. The baseline information and clinical outcomes were obtained. Patients were divided into survivor group and non-survivor group according to whether they died during ICU hospitalization. Results The serum Mrp 8/14 levels were significantly increased in the non-survivor group compared to the survivor group (P < 0.05). Logistic regression analysis showed that serum Mrp 8/14, albumin and APACHE II were the independent factors for predicting the prognosis of sepsis-induced ARDS during ICU hospitalization after adjustment. Additionally, the area under the receiver operating characteristic curve for Mrp 8/14 combined with albumin was associated with ICU mortality and was higher than that of Mrp 8/14, albumin, APACHE II and Mrp 8/14 combined with APACHE II (all P < 0.05). A nomogram was constructed to predict ICU mortality and the c-indexes of predictive accuracy was 0.830 in the cohort (P < 0.05). Conclusions The serum Mrp 8/14 upon ICU admission in septic patients may be useful for predicting mortality in sepsis-induced ARDS patients during ICU hospitalization.